2019
DOI: 10.21203/rs.2.13119/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Colchicine causes prenatal cell toxicity and increases tetraploid risk

Abstract: Background Colchicine is a clinical medicine used for relief from gout and familial Mediterranean fever. Because of its toxic effects, intravenous injection of colchicine has been banned, but it is still widely administered orally. We assayed the toxic effects of colchicine in cultured primary chorionic villus cells and amniotic fluid cells to interpret its influence on the placenta and foetus. Methods Bright field record and cell count kit 8 were used to value cell viability. Flow cytometer was used to identi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In this study, we tested duloxetine's neural cell toxicity in the mouse neuroblastoma cell line N2a and mouse C17.2 neural stem cells. These specific cells were good models for the evaluation of clinical drug toxicity [16]. The results showed significant cell toxicity in both cell lines when they were exposed to 100 μM duloxetine, and the C17.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we tested duloxetine's neural cell toxicity in the mouse neuroblastoma cell line N2a and mouse C17.2 neural stem cells. These specific cells were good models for the evaluation of clinical drug toxicity [16]. The results showed significant cell toxicity in both cell lines when they were exposed to 100 μM duloxetine, and the C17.…”
Section: Discussionmentioning
confidence: 99%
“…They are also risk components that cause reproductive toxicity. In an in vitro study, colchicine exerts toxic effects on cultured primary chorionic villus cells and amniotic fluid cells (Wang, Xie, et al, 2019). Collective studies confirmed α‐solanine impairs the functions of human trophoblast cells and inhibits cell proliferation in mouse testis in vivo and in vitro (Chen et al, 2021; Park et al, 2019).…”
Section: Classification On the Risk Components In Tcm‐induced Reprodu...mentioning
confidence: 99%
“…MSCs can be derived from various tissues; while they meet the criteria of MSCs and have effective therapeutic effects in animal models, there are still some differences in morphology and biological function [16,17]. The amniotic fluid cells (AFCs) of the second trimester could be cultured in dishes for several passages, which have been used for classical cytogenetic prenatal diagnosis [18]. In previous work, we identified AFCs as a kind of MSC (AF-MSC) that express MSC-specific biomarkers and can be induced to differentiate into mesodermal terminal cells and inhibit PHA-(phytohemagglutinin-) activated PBMC (peripheral blood mononuclear cell) division [19].…”
Section: Introductionmentioning
confidence: 99%